Role of sutureless aortic valve replacement in the era of transcatheter valves - B. S. Tsaroev; A. V. Bogachev-Prokofiev; R. M. Sharifulin; A. V. Afanasyev; A. M. Chernyavsky (Российский кардиологический журнал, 2023)
This review article considers the role of sutureless aortic valve replacement in the era of transcatheter replacement. Modern data regarding the outcomes of treatment with these two methods and its comparison are considered. Their main disadvantages and the cohorts of patients suitable for each technique are determined.